Answer :

Answer:

f(x) = -2x + 1

Step-by-step explanation:

The given expression is [tex]\frac{64^x}{4^{5x-1}}[/tex]

By solving the given expression further,

[tex]\frac{64^x}{4^{5x-1}}[/tex] = [tex]\frac{[(4)^{3}]^x}{(4)^{5x-1}}[/tex] [Since 64 = 4³]

        = [tex]\frac{4^{3x}}{4^{5x-1}}[/tex]

        = [tex]4^{3x}\times 4^{-(5x-1)}[/tex] [Since [tex]\frac{1}{a}=a^{-1}[/tex]]

        = [tex]4^{3x-5x+1}[/tex] [Since [tex]a^x\times a^y=a^{(x+y)}[/tex]]

        = [tex]4^{(-2x+1)}[/tex]

By comparing the result with [tex]4^{\text{f(x)}}[/tex]

f(x) = -2x + 1

Therefore, f(x) = (-2x + 1) will be the answer.

Other Questions